2008
DOI: 10.1111/j.1365-246x.2008.03725.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme sensitivity of crosshole electrical resistivity tomography measurements to geometric errors

Abstract: S U M M A R YThe effects of geometric errors on crosshole resistivity data are investigated using analytical methods. Geometric errors are systematic and can occur due to uncertainties in the individual electrode positions, the vertical spacing between electrodes in the same borehole, or the vertical offset between electrodes in opposite boreholes. An estimate of the sensitivity to geometric error is calculated for each of two generic types of four-electrode crosshole configuration: current flow and potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…Research is currently being carried on using the 3-D array optimization algorithm for surveys with subsurface electrodes using conventional vertical boreholes (Wilkinson et al 2008), as well as along horizontal lines of subsurface electrodes (Harro & Kruse 2013). As these surveys involve electrodes on different lines, it will also be necessary to use the geometric factor relative error to filter out potentially unstable arrays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research is currently being carried on using the 3-D array optimization algorithm for surveys with subsurface electrodes using conventional vertical boreholes (Wilkinson et al 2008), as well as along horizontal lines of subsurface electrodes (Harro & Kruse 2013). As these surveys involve electrodes on different lines, it will also be necessary to use the geometric factor relative error to filter out potentially unstable arrays.…”
Section: Resultsmentioning
confidence: 99%
“…Wilkinson et al (2008) found that for cross-borehole surveys it was necessary to set a limit on the sensitivity of the array geometric factor to errors in the position of the electrodes as well to remove arrays that are likely to be unstable. As 3-D surveys involve cross-line measurements, we also use this method.…”
Section: Use Of the Geometric Factor Relative Error For 3-d Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…In these experiments, the distance between adjacent electrodes in the tank setup was only 0.05 meter (50 mm). Small errors in the positions of the electrodes and their finite sizes can have significant effects on the results for certain cross-borehole configurations (Wilkinson et al 2008). To minimize these geometric errors, the electrodes were mounted on rigid rods and anchored to fixed points on the base of the tank.…”
Section: Experimental Data Setsmentioning
confidence: 99%
“…Among them, the Electrical Resistivity Tomography (ERT) is considered as one the most efficient techniques in imaging such properties and processes associated to subsurface geoelectrical structure (Daily et al, 1992;Park, 1998;Muller et al, 2003;Singha and Gorelick, 2005;Mohnke et al, 2006;Nguyen et al, 2009). In order to eliminate limitations of resolution decrease with increasing depth of investigation, ERT techniques based on variations of borehole, surface-to-borehole and cross-hole measurements, have been proposed (Asch and Morrison, 1989;Daily and Owen, 1991;Slater et al, 2000;Zhou and Greenhalgh, 2000;Friedel et al, 2004;Marescot et al, 2002;Tsourlos et al, 2004Tsourlos et al, , 2005Wilkinson et al, 2008). Along with spatial, ways for time resolution extent with time-lapse techniques, have been reported to literature (Tsourlos et al, 2003(Tsourlos et al, , 2005Oldenborger et al, 2007).…”
Section: Introductionmentioning
confidence: 99%